Tissue paper from banana peels: a preliminary study - Muhamad, Aida; Mohd Noor, Siti Fatimah; Abdul Halim, Norhazimah; Md Samad, Nur Afiqah; Ibrahim, Nurul Fatihah; Abu Bakar, Syahirah Amirah (Penerbit UTHM, 2020)
Banana was originally from Malaysia and it is a herbaceous plant of the genus of Musa and family of Musaceae. Banana is contributing 16% of the world’s total fruit productions [1]. The cultivation of the banana plant is mainly for its fruits. In some countries, banana fruit and its peel are considered to be the golden fruit of nature because they are providing healthy digestion and promote natural beauty to the body with essential nutrients. Moreover, banana fruit help in preventing anemia, stress, ulcers, and other minor illness. Banana is also considered to be a functional food source against cancer and heart disease and a good source of natural antioxidants for foods [2]. A large quantity of bananas is produced annually and its peel, which accounts for about 35% of the whole fruit weight, is mostly discarded as waste. Approximately 36 million tonnes of banana peel is generated every year and this is a potential material for further utilisation [3].